MENINGKATKAN PENGETAHUAN KONSEPTUAL DAN PENGETAHUAN PROSEDURAL MAHASISWA MELALUI PENDEKATAN DISKURSUS MATEMATIK - Hamdani, Hamdani (Universitas Tanjungpura, 2015)
This research aim to raise conceptual and procerural knowledge students through mathematical discouse approach. This study involving the students third semester of mathematic programme in Training and Education Faculty. To achieve goal, this study was used to action research method. Instrument in this study consist of observer worksheet and test. Result of this study show that (i) competency of conceptual knowledge was multiplying from 10,3 % (fisrt cycle) to 75,8 % (second cycle) in good or best category; (ii) competency of procedural knowledge was multiplying from 31,1 % (fisrt cycle) to 93 % (second cycle) in good or best category Key word: Conceptual knowledge, procedural knowledge.